Controlling lean manufacturing in multidivisional organisations: Highlighting local interests and constraints. Issue 11 (5th November 2018) - van der Steen, Martijn Pieter; Tillema, Sandra
Abstract : Purpose: The purpose of this paper is to address the impact of a multidivisional structure on the implementation of lean manufacturing. It investigates how the controls employed by the corporate level impact the local implementation of lean manufacturing. Design/methodology/approach: The paper reports on case studies in three subsidiaries in different multidivisional organisations. Findings: The paper finds that lean manufacturing can be severely constrained by the accounting-based controls which are commonly in place in a multidivisional structure. Depending on the degree of centralisation, subsidiaries may be restricted to implementing lean tools in a fragmented way, rather than acting according to a coherent set of principles. Practical implications: Companies may have to accept that being part of a multidivisional organisation can imply that their lean implementation is more gradual and piecemeal than they prefer. The paper proposes several ways to mitigate the constraints that may arise from incompatibilities between accounting-based controls and lean controls. Originality/value: This study contributes to the literature about external constraints on production innovations, such as lean manufacturing. It highlights how the organisational context creates local conditions that may be detrimental to the implementation of lean manufacturing.